Identification of a novel chromosome-encoded fosfomycin resistance gene fosC3 in Aeromonas caviae - Lu, Junwan; Zhang, Runzhi; Yu, Yan; Lou, Hongqiang; Li, Dong; Bao, Qiyu; Feng, Chunlin (Frontiers in Microbiology, 2025)
BackgroundOwing to the rapid emerging of multidrug-, even pandrug-resistant pathogens, and lack of new antibiotics, the older antibiotic, fosfomycin, has been reused in recent years in the clinical practice, especially for treatment of uropathogen infections. With the increased use of fosfomycin, bacterial resistance to it has also increased drastically. Elucidating the resistance mechanism to the antimicrobial has become an urgent task.MethodsThe putative fosfomycin resistance gene fosC3 was cloned, and minimal inhibitory concentrations were determined by the agar dilution method. Enzyme kinetic parameters were measured by high-performance liquid chromatography. Bioinformatics analysis was applied to understand the evolutionary characteristics of FosC3.ResultsThe A. caviae strain DW0021 exhibited high level resistance to several antimicrobials including kanamycin, streptomycin, chloramphenicol, florfenicol, tetracycline, and especially higher to fosfomycin (> 1,024 μg/mL), while genome annotation indicated that no function-characterized resistance gene was associated with fosfomycin resistance. A novel functional gene designated fosC3 responsible for fosfomycin resistance was identified in the chromosome of A. caviae DW0021. Among the function-characterized proteins, FosC3 shared the highest amino acid similarity of 58.65% with FosC2. No mobile genetic element (MGE) was found surrounding the fosC3 gene. The recombinant pMD19-fosC3/DH5α displayed a MIC value of 32 μg/mL to fosfomycin, which revealed a 128-fold increase of MIC value to fosfomycin compared to the control pMD19/E. coli DH5α (0.25 μg/mL). FosC3 was phylogenetically close to FosC2 and exhibited a kcat and Km of 82,442 ± 1,475 s−1, 70.99 ± 4.31 μM, respectively, and a catalytic efficiency of (1.2 ± 0.3) × 103 μM−1·s−1.ConclusionIn this work, a novel functional fosfomycin thiol transferase, FosC3, which shared the highest protein sequence similarity with FosC2, was identified in A. caviae. The fosfomycin inactivation enzyme FosC3 could effectively inactivate fosfomycin by chemical modification. It is implied that such mechanism facilitates A. caviae to respond to fosfomycin exposure, thereby enhancing survival. However, fosC3 was not related with any MGE, which differs from many other fosfomycin thiol transferase genes. As a result, fosC3 is not expected to be transmitted to other species through horizontal gene transfer mechanism. Our findings will contribute to the resistance mechanism of the common pathogenic A. caviae.